2020
DOI: 10.22596/erj2020.05.01.8.26
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Processes of High School Students to do Proof without Words

Abstract: There are opinions about approaching the proof in mathematics education need to change as providing students to understand the mathematical proof rather than developing formal mathematical proof skills. In this context, proofs without words described as informal proofs can be used in proof teaching. The purpose of this study was to investigate the processes of high school students to do proofs without words. This study was designed as the case study a high school in Turkey. Consequently, activities of proof wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Researchers of this study, in their previous studies, obtained results about the difficulty in proof without words at all levels. They observed that students cannot generalize from a single example situation given in the visual (Demircioglu and Polat, 2015;Demircioglu and Polat, 2016;Polat and Akgün, 2020). In order to examine this problem, the data collection tool selected, and the explanations of the preservice mathematics teachers about the proof without words analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers of this study, in their previous studies, obtained results about the difficulty in proof without words at all levels. They observed that students cannot generalize from a single example situation given in the visual (Demircioglu and Polat, 2015;Demircioglu and Polat, 2016;Polat and Akgün, 2020). In order to examine this problem, the data collection tool selected, and the explanations of the preservice mathematics teachers about the proof without words analyzed.…”
Section: Methodsmentioning
confidence: 99%